2021
DOI: 10.4081/jphr.2021.2181
|View full text |Cite
|
Sign up to set email alerts
|

High-Fructose Diet Initially Promotes Increased Aortic Wall Thickness, Liver Steatosis, and Cardiac Histopathology Deterioration, but Does Not Increase Body Fat Index

Abstract: Background: Dietary fats and fructose have been responsible for inducing obesity and body tissues damage due to the consequence of metabolic syndrome through several mechanisms. The body fat index (BFI) is one of the anthropometric measures used to detect obesity in rats. This study aims to examine the correlation between high-fat high-fructose diet and liver steatosis cell count, early atherosclerosis characteristics, and BFI in Sprague Dawley Rats.Design and methods: This was an experimental design using 2 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…The HFD group (G2) had the highest RW with a significantly difference values compared by the control group (see Figure 8, h). Additionally, hydropic degeneration in cardiac muscle found in Microphotograph of rat heart in Figure (8, b) that might be a result of excess consuming of fructose which represented a hazard agent for the consequence of metabolic syndrome through several mechanisms with dysfunctions in various organs and tissues as heart, these results found to be in agreement with Handayani et al [58] as they reported that dietary fat and fructose consumption promote atherosclerosis and cardiac histopathology alteration. Photomicrographs of treated groups with CMCTS+HA and AuNPs fig.…”
Section: Histopathology and Relative Weight Of The Heartsupporting
confidence: 82%
“…The HFD group (G2) had the highest RW with a significantly difference values compared by the control group (see Figure 8, h). Additionally, hydropic degeneration in cardiac muscle found in Microphotograph of rat heart in Figure (8, b) that might be a result of excess consuming of fructose which represented a hazard agent for the consequence of metabolic syndrome through several mechanisms with dysfunctions in various organs and tissues as heart, these results found to be in agreement with Handayani et al [58] as they reported that dietary fat and fructose consumption promote atherosclerosis and cardiac histopathology alteration. Photomicrographs of treated groups with CMCTS+HA and AuNPs fig.…”
Section: Histopathology and Relative Weight Of The Heartsupporting
confidence: 82%
“…Regular fructose intake contributes to the development of lipid disorders, oxidative stress, and mild chronic inflammation, which are directly associated with obesity, NAFLD, and cardiovascular diseases [24]. This concern is supported by observations in human and rodent epidemiological studies that HFrD induces hepatic intrahepatocellular lipids, hepatic DNL, and abdominal aortic thickness, and increases hepatic insulin resistance [25][26][27]. Furthermore, consistent with our data, several studies have reported that HFrD-fed rats have increased hepatic levels of upstream regulators of DNL, such as SREBP-1, ChREBP, key lipogenic enzymes, and pro-inflammatory cytokines [28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 95%
“…Since fructose largely replaced sucrose as a source of sweeteners in soft drinks in the 1970's, an association between high-fructose corn syrup consumption and obesity became increasingly observed ( 98 ). In addition, beyond increasing hepatic steatosis, fructose enhances aortic wall thickness and foam cell count in Sprague-Dawley rats fed a high-fat diet ( 99 ). Van den Hoek and colleagues fed Ldlr −/− .Leiden mice an obesogenic diet for 28 weeks containing 41% calories from fat, 0.05% cholesterol, and 44% calories from fructose ( 100 ), which recapitulated multiple aspects of NASH like inflammation ( 100 ), fibrosis ( 101 ), and circulating AST and ALT ( 102 ), as well as established atherosclerotic lesions ( 100 ).…”
Section: Concurrent Modelling Of Nash and Atherosclerosismentioning
confidence: 99%
“…Since fructose largely replaced sucrose as a source of sweeteners in soft drinks in the 1970's, an association between high-fructose corn syrup consumption and obesity became increasingly observed (98). In addition, beyond increasing hepatic steatosis, fructose enhances aortic wall thickness and foam cell count in ).…”
Section: Diets In Excess or Deficiency: Which Is Ideal?mentioning
confidence: 99%